(untitled) (The Review of Diabetic Studies, 2024)
The advent of telehealth technology has revolutionized patient care in nursing practice, offering unprecedented opportunities for enhanced healthcare delivery and access. This review explores the significant advancements in telehealth utilizing secondary data sources, highlighting its transformative impact on nursing practice. Over recent years, telehealth has evolved from a supplementary tool to a critical component of healthcare systems, driven by technological innovations, policy changes, and the growing demand for accessible healthcare. The study examines key areas such as remote patient monitoring, virtual consultations, and digital health interventions, discussing how these innovations have improved patient outcomes, increased healthcare accessibility, and optimized resource utilization. Furthermore, it addresses the challenges and limitations faced by healthcare providers, including issues of data security, digital literacy, and the digital divide. By analyzing current trends and case studies, this review underscores the vital role of telehealth in enhancing patient-centered care and the need for ongoing research and policy development to fully realize its potential. The findings indicate that telehealth not only supports the professional growth of nurses through new skill sets but also encourages a more proactive, preventive approach to patient care, positioning it as a cornerstone of modern nursing practice.